Read the clonotype: Next-generation sequencing-based lymphocyte clonality analysis and perspectives for application in pathology - Groenen, Patricia J. T. A.; van den Brand, Michiel; Kroeze, Leonie I.; Amir, Avital L.; Hebeda, Konnie M. (Frontiers in Oncology, 2023)
Clonality assessment using the unique rearrangements of immunoglobulin (IG) and T-cell receptor (TR) genes in lymphocytes is a widely applied supplementary test for the diagnosis of B-cell and T-cell lymphoma. To enable a more sensitive detection and a more precise comparison of clones compared with conventional clonality analysis based on fragment analysis, the EuroClonality NGS Working Group developed and validated a next-generation sequencing (NGS)-based clonality assay for detection of the IG heavy and kappa light chain and TR gene rearrangements for formalin-fixed and paraffin-embedded tissues. We outline the features and advantages of NGS-based clonality detection and discuss potential applications for NGS-based clonality testing in pathology, including site specific lymphoproliferations, immunodeficiency and autoimmune disease and primary and relapsed lymphomas. Also, we briefly discuss the role of T-cell repertoire of reactive lymphocytic infiltrations in solid tumors and B-lymphoma.